Constructing Escherichia coli co-display systems for biodegradation of polyethylene terephthalate - Jiayu Hu; Yijun Chen (Bioresources and Bioprocessing, 2023)
Abstract Background The accumulation of fast-growing polyethylene terephthalate (PET) wastes has posed numerous threats to the environments and human health. Enzymatic degradation of PET is a promising approach for PET waste treatment. Currently, the efficiency of various PET biodegradation systems requires further improvements. Results In this work, we engineered whole cell systems with co-display of strong adhesive proteins and the most active PETase for PET biodegradation in E. coli cells. Adhesive proteins of cp52k and mfp-3 and Fast-PETase were simultaneously displayed on the surfaces of E. coli cells, and the resulting cells displaying mfp-3 showed 50% increase of adhesion ability compared to those without adhesive proteins. Consequently, the degradation rate of E. coli cells co-displaying mfp-3 and Fast-PETase for amorphous PET exceeded 15% within 24 h, exhibiting fast and thorough PET degradation. Conclusions Through the engineering of co-display systems in E. coli cells, PET degradation efficiency was significantly increased compared to E. coli cells with sole display of Fast-PETase and free enzyme. This feasible E. coli co-display system could be served as a convenient tool for extending the treatment options for PET biodegradation. Graphical Abstract